Impact of recycled aggregates on mechanical properties of concrete. (2023) - Mathur, Pulkit; Joshi, Tejas; Dave, Urmil
Abstract: The voluminous disposal of demolition waste into landfills is proving to be an owing cause of environmental pollution. An essential outlook for economic construction is the processing of the waste procured from construction works to preserve an ecological balance. To contribute towards research to generate sustainable reusable construction products, an attempt was made to analyse the feasibility of recycled coarse aggregates (RCA) as a substitute for coarse aggregate. An experiment has been conducted to develop sustainable concrete grade M30 conforming to Indian Standards. The partial replacement was carried out using C&D waste extracted from the nearby dump yard in the vicinity of Ahmedabad city and processed at a nearby recycling plant. This C & D waste was from recent collapse of one of the girder of bridge. In this present investigation an attempt was carried out to check the feasibility of the 40 days old RCA on the properties of M 30 grade of concrete. A total of 5 batches were produced with a 10 % increment of RCA. The physical properties of natural and RCA were compared. A comparative analysis between the hardened properties of the control mix and recycled aggregate concrete (RAC) was performed. Test parameters determined to study the impact of recycled aggregate were compressive strength, flexural strength, and split tensile strength. It was observed that the specific gravity and water absorption of recycled aggregates (R.A.) were lower and higher, respectively, in contrast to natural coarse aggregate. The results prove that the performance of concrete containing recycled constituents was largely affected by the properties and quality of aggregate and deviates slightly towards the lower end of the desired level but reduces the environmental impact of disposal.